DEGRADATION OF DYES CONTAMINATED AN AQUEOUS SOLUTION USING LACCASE SUPPORTED ON LOCAL PORCELAINTE - Tlaiaa, Younis Swadi.; Ridha , M. J. M-; Hussein , S. I. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
This research explores an efficient decolorization approach of aqueous solution containing Reactive Navy Blue (RNB), Reactive Red (RR), Reactive Turquoise Blue (RTB), and Reactive Black (RB) dyes by employing laccase immobilized on granular Porcelanite (PC). The process of immobilizing the laccase enzyme from Fenugreek seeds onto Porcelanite was achieved through a covalent method and the immobilization ratio was reached to 98%. PC function groups and surface texture was examined using Scanning electron microscope (SEM) and Fourier transform infrared (FT-IR) techniques. The impact of several process parameters, including pH, particle amount, dye concentration, and temperature, were investigated. The treatment successfully led to maximum decolorization rates of 95.50% for RB, 90.19% for RNB, 85.63% for RTB, and 80.82% for RR after only 24 hours, in which the best conditions were (5, 1.5 g, 50 mg/l,25 ◦C, respectively (. Interestingly, the coefficient of determination (R2) for RB, RNB, RTB, and RR dyes was 87%, 82%, 87%, and 72%, respectively, indicating high model predictivity of the behavior of dyes post-decolorization, indicating enhanced wastewater remediation via laccase immobilization.